New insights about the role of Na–K ratio on the vibrational dynamics of synthetic‐basalt glasses. (5th January 2022) - Cassetta, Michele; Zanatta, Marco; Biesuz, Mattia; Giarola, Marco; Mariotto, Gino
Abstract: Basalts are among the most abundant igneous rocks on Earth. Originated from the rapid cooling of magma erupted by volcanoes, they are increasingly used as raw materials in glass and ceramic technology due to their unique physico‐chemical properties. The characteristics of basalts, like the glass transition temperature, are strongly controlled by their structure, which is a function of composition. Therefore, the investigation of the interplay between the intimate structure and the mechanical and physical properties of basalt glasses is of paramount importance in view of their industrial exploitation. Here, we present a Raman study of a set of synthetic‐basalt glasses in which the occurrence of small chemical variations appreciably affects their glass transition temperature. We analyzed the Raman spectra focusing on both the spectral regions of the so‐called nonbridging oxygens and of the boson peak. We show the existence of a scaling law for the boson peak of four synthetic‐basalt glasses, and we infer from its breakdown the occurrence of a deep reorganization of the glass structure resulting from the Na–K replacement in the network, despite small variations of the other major elements. Abstract : (a) Reduced low‐wavenumber cross polarized Raman spectra of basalt glasses with different Na–K ratios. (b) Relationship between the Tg, the boson peak position (ωBP), and the squeezing wavenumber (ωS) obtained by fitting the low‐wavenumber region to a log‐normal function and by the scaling procedure. Numerical values indicate the different Na–K ratios for the different glasses.